Genomic insight into the origin, domestication, dispersal, diversification and human selection of Tartary buckwheat - Yuqi He; Kaixuan Zhang; Yaliang Shi; Hao Lin; Xu Huang; Xiang Lu; Zhirong Wang; Wei Li; Xibo Feng; Taoxiong Shi; Qingfu Chen; Junzhen Wang; et al. (Genome Biology, 2024)
Abstract Background Tartary buckwheat, Fagopyrum tataricum, is a pseudocereal crop with worldwide distribution and high nutritional value. However, the origin and domestication history of this crop remain to be elucidated. Results Here, by analyzing the population genomics of 567 accessions collected worldwide and reviewing historical documents, we find that Tartary buckwheat originated in the Himalayan region and then spread southwest possibly along with the migration of the Yi people, a minority in Southwestern China that has a long history of planting Tartary buckwheat. Along with the expansion of the Mongol Empire, Tartary buckwheat dispersed to Europe and ultimately to the rest of the world. The different natural growth environments resulted in adaptation, especially significant differences in salt tolerance between northern and southern Chinese Tartary buckwheat populations. By scanning for selective sweeps and using a genome-wide association study, we identify genes responsible for Tartary buckwheat domestication and differentiation, which we then experimentally validate. Comparative genomics and QTL analysis further shed light on the genetic foundation of the easily dehulled trait in a particular variety that was artificially selected by the Wa people, a minority group in Southwestern China known for cultivating Tartary buckwheat specifically for steaming as a staple food to prevent lysine deficiency. Conclusions This study provides both comprehensive insights into the origin and domestication of, and a foundation for molecular breeding for, Tartary buckwheat.